Fungal Contamination Of Spices Used In Local Malaysian Cuisines - Nordin, Syamilah (Universiti Sains Malaysia, 2021)
Spices are widely used in various cuisines in Malaysia to enhance the flavour and aroma of the cuisines. However, spices are susceptible to fungal infection and subsequent mycotoxin contamination if the storage conditions are favorable for the fungal growth. Thus, this study aimed to determine the prevalence of mycotoxigenic fungi in spices used in Malaysian local cuisines and to identify the species based on morphological characteristics. A total of 48 samples that consist of ground spices and whole spices were purchased randomly at the retail market in Penang. The level of fungal contamination in ground and whole spices were analyzed using dilution plating method, and direct plating method, respectively. Based on the direct plating results, cumin (4.0 × 103 CFU/g) recorded the highest total fungal load, followed by black pepper (3.6 × 103 CFU/g) and coriander seed (3.3 × 103 CFU/g). Meanwhile, the highest incidence of fungal infection for the whole spices was recorded by coriander seed (91%) followed by black pepper (90%) and white pepper (87%). In contrast, star anise and cloves were free from fungal contamination. A. niger was the predominant species found in kurma mix and curry powder with the isolation frequency of 72% and 65% respectively. A. niger is described as black colonies with inconspicuous mycelium on Czapek Yeast Autolysate (CYA) and Malt Extract Agar (MEA). In addition, A. carbonarius, A. chavelieri, and A. tamarii were also isolated from other spices such as black pepper and coriander seeds with lower isolation frequency. A. niger is the most common mycotoxigenic fungi that produce ochratoxin A, which is classified as a potential human carcinogen (Group 2B). These findings might indicate the risk of ochratoxin exposure to the consumers since spices are commonly used in various local cuisines in Malaysia.